Complication Profiles by Mastectomy Indication in Tissue Expander Breast Reconstruction. Issue 4 (April 2019) - Chouairi, Fouad; Gabrick, Kyle S.; Avraham, Tomer; Markov, Nickolay P.; Alperovich, Michael
Abstract : Background: Two-stage implant breast reconstruction is the most commonly performed breast reconstruction procedure. Limited data exist regarding reconstruction complication rates examined by mastectomy indication. Methods: Patients who underwent two-stage implant breast reconstruction at Yale New Haven Hospital from 2011 to 2017 were included in the study. Perioperative complications were compared. Chi-square analysis, t tests, and Fisher's exact tests were used to determine significant associations. A binary logistic regression was used to determine variables with a significant impact on the likelihood of mastectomy flap necrosis. Results: Between 2011 and 2017, complete perioperative records were available for 141 patients who underwent 226 mastectomies followed by two-stage tissue expander/permanent implant reconstruction. Of the 226 mastectomies, 134 were therapeutic and 92 were prophylactic. On regression analysis, there were no significant differences in demographics, comorbidities, or mastectomy and reconstructive details between the two breast groups except for there being more modified radical mastectomies in therapeutic breasts ( p = 0.003). When comparing complications, there was a significantly higher risk of mastectomy flap necrosis in the therapeutic group ( p = 0.017). Therapeutic mastectomies had a 9.5 times higher risk of mastectomy flap necrosis than prophylactic mastectomies when adjusted for confounding variables. There were no significant differences in other reconstructive complications between the two groups. Conclusions: Patients undergoing therapeutic mastectomies have a significantly higher risk of mastectomy flap necrosis than those undergoing prophylactic mastectomies. Although the underlying cause still needs to be determined, differences in technique may be related to mastectomy flap necrosis. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.